Anti-oxidative and anti-inflammatory activities of the ethanol extract of edible flower from Chimonanthus praecox - Kang, Yuan; Liu, Zhuangzhuang; Li, Wenjing; Li, Ximeng; Zhang, Xiaoyu; Xu, Zhenlu; Gao, Yuan; Qi, Yun (Frontiers in Pharmacology, 2022)
Chimonanthi Praecocis Flos, namely wintersweet flower, is the edible flower or flower bud of Chimonanthus praecox (L.) Link which is a deciduous shrub plant originated from China and is widely cultivated as a garden or ornamental plant all over the world. However, few studies focused on its anti-inflammatory property. In the present study, we explored the anti-inflammatory and anti-oxidative activities of ethanol extract of Chimonanthi Praecocis Flos (CPE) which contained 7.980% ± 0.176% total flavonoids and 1.461% ± 0.041% total alkaloids. In LPS-stimulated RAW264.7 macrophages, CPE significantly decreased the productions of NO and prostaglandin E2 (PGE2) through reducing the expressions of their synthases—inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2). It also suppressed the transcription and translation of pro-inflammatory cytokines interleukin-1β (IL-1β) and interleukin-6 (IL-6). Further research revealed that CPE impeded the phosphorylation and degradation of IκBα, thus restraining the nuclear translocation of p65, and consequently dampening NF-κB signaling. In endotoxemia mice, several pro-inflammatory cytokines in serum were also decreased after CPE treatment. Besides anti-inflammatory activity, anti-oxidative activity is another important capacity of wintersweet flower. Indeed, CPE reduced LPS-elevated intracellular total reactive oxygen species (ROS) level by weakening NADPH oxidase activity in cell system. Moreover, it directly scavenged DPPH radical and superoxide anion, and exerted ferric reducing ability in cell-free system. Our findings demonstrate that wintersweet flower can be used as a beneficial natural product or an additive by virtue of its anti-oxidative and anti-inflammatory properties.